Telephone triage protocols for nurses - Briggs, Julie K. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"Performing telephone triage requires the ability to make quick and effective decisions based on limited information.This rapid-access resource delivers over 200 triage protocols for evaluating patients' symptoms over the telephone. Each symptom entry lists questions, grouped by urgency level, to determine whether the caller should seek emergency care immediately, seek medical care the same day, call back for appointment, or follow home care instructions. Detailed home care instructions are then provided. Simple, direct, and useful, it is the most comprehensive and user-friendly telephone triage book available. This new edition features several new protocols--Swine Flu (H1N1 virus), Bedbug Problems, Tattoo Problems, and Emergency Contraception--as well as new information in the introductory chapter about program development, management issues, and staff development, including training. Also featured is a new reminder about documentation in each protocol as well as a new anatomic Table of Contents and expanded home care instructions"--